The role of trans obturator tape as a surgical procedure for female stress urinary incontinence and its impact on quality of life in Jammu region - Puri, Sapna; Kohli, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Stress incontinence is one of the most common but debilitating health issue among women. It has a detrimental effect on overall health and quality of life of women. Trans obturator tape (TOT) has emerged as a promising treatment modality. The aim of present study was to assess the usefulness of TOT in terms of change in quality of life of stress incontinence patients. Methods: The study was performed at Department of Obstetrics and Gynecology, Acharya Shri Chandler of Medical Sciences (ASCOMS), Jammu. A total of 50 symptomatic women were enrolled in the study and underwent TOT procedure using outside-in technique. The quality of life of women was assessed at enrolment and 12 months after the procedure using King’s Health Questionnaire (KHQ). Change in QOL was assessed using paired ‘t’-test. Results: After 12 months follow-up, a total of 27 (54%) patients were entirely symptom free. As compared to pre-treatment QOL assessment on KHQ for general health/incontinence impact, quality of life and symptom scores a % decline of 73.2%, 79.8% and 78.4% was observed. For all the three parts, the change in scores was significant statistically. No other complications and side effects were reported. Conclusions: TOT is a useful procedure which provided symptomatic relief as well as QOL enhancement.